Joint space width of the tibiotalar joint in the healthy foot - Imai, Kan (J Foot Ankle Res, 2015)
BACKGROUND: It is important to evaluate dynamic changes in the joint space width of the ankle mortise in detail in order to better understand the pathology of foot and ankle disorders. However, there are few reports on changes in the joint space width of the foot and ankle assessed using 3D images. The purpose of this study was to determine the changes in the joint space width of the ankle (tibiotalar joint) in association with dorsiflexion and plantar flexion of the ankle joint in healthy feet. METHODS: Computed tomography (CT) images of 10 healthy feet were obtained in the neutral, plantarflexed and dorsiflexed positions of the ankle joint, from which 3D virtual models were fabricated of the tibia, fibula and talus. The 3D joint space width in these models was calculated using a custom made software program. RESULTS: The joint space width increased in the order of dorsiflexion, neutral position and plantar flexion. Regarding the amount of change in dorsiflexion and plantar flexion relative to the neutral position, there were no significant differences in the middle-middle position. On the other hand, there were highly significant differences in the medial-anterior, medial-middle and medial-posterior positions. CONCLUSIONS: The joint space width of the ankle joint can be calculated accurately using 3D reconstruction images. Our findings should assist in clarifying pathology associated with movement of the ankle during the gait cycle based on changes in the joint space width in feet exhibiting disorders.